Evolução em pacientes internados do Instituto Bairral na cidade de Itapira-Sp entre 1997 e 2010 com diagnóstico de dependência em crack e álcool - Moreira, Marcio Mariano [UNIFESP] (2018)
Objectives: to verify the evolution in patients sus (unified health system) hospitalized in the Bairral Institute and Taipas General Hospital from 1997 to 2010; assemble a database for a qualitative-quantitative study; to analyze the data for women admitted to the first hospital stay in order to understand the pattern in the consumption of psychoactive substances; to identify the psychoactive substances used by patients before being hospitalized; to calculate the standartized mortality ratio in patients hospitalized for the first time at Instituto Bairral de Itapira due to the use of crack; to calculate the standartized mortality ratio in patients hospitalized for the first time at Instituto Bairral de Itapira due to alcohol use. methods: longitudinal study - alcohol: 3229 individuals divided into 2826 (87.52%) men and 403 (12.48%) women hospitalized for the first time due to alcohol consumption (icd10 - f10); crack - 552 subjects divided into 396 (71.74%) men and 156 (28.26%) women hospitalized for the first ...